Functional Characterization of a Flavone Synthase That Participates in a Kumquat Flavone Metabolon - Tian, Shulin; Yang, Yuyan; Wu, Tao; Luo, Chuan; Li, Xin; Zhao, Xijuan; Xi, Wanpeng; Liu, Xiaogang; Zeng, Ming (Frontiers in Plant Science, 2022)
Flavones predominantly accumulate as O- and C-glycosides in kumquat plants. Two catalytic mechanisms of flavone synthase II (FNSII) support the biosynthesis of glycosyl flavones, one involving flavanone 2-hydroxylase (which generates 2-hydroxyflavanones for C-glycosylation) and another involving the direct catalysis of flavanones to flavones for O-glycosylation. However, FNSII has not yet been characterized in kumquats. In this study, we identified two kumquat FNSII genes (FcFNSII-1 and FcFNSII-2), based on transcriptome and bioinformatics analysis. Data from in vivo and in vitro assays showed that FcFNSII-2 directly synthesized apigenin and acacetin from naringenin and isosakuranetin, respectively, whereas FcFNSII-1 showed no detectable catalytic activities with flavanones. In agreement, transient overexpression of FcFNSII-2 in kumquat peels significantly enhanced the transcription of structural genes of the flavonoid-biosynthesis pathway and the accumulation of several O-glycosyl flavones. Moreover, studying the subcellular localizations of FcFNSII-1 and FcFNSII-2 demonstrated that N-terminal membrane-spanning domains were necessary to ensure endoplasmic reticulum localization and anchoring. Protein–protein interaction analyses, using the split-ubiquitin yeast two-hybrid system and bimolecular fluorescence-complementation assays, revealed that FcFNSII-2 interacted with chalcone synthase 1, chalcone synthase 2, and chalcone isomerase-like proteins. The results provide strong evidence that FcFNSII-2 serves as a nucleation site for an O-glycosyl flavone metabolon that channels flavanones for O-glycosyl flavone biosynthesis in kumquat fruits. They have implications for guiding genetic engineering efforts aimed at enhancing the composition of bioactive flavonoids in kumquat fruits.